(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Japanese writer Kobo Abe’s novel "Woman in the Sand" has been translated into Uzbek with great skill. This work has been translated into many languages and is included in the list of masterpieces of Japanese literature. Interpreted by researchers as a complex work, this novel provides an in-depth analysis of the eternal conflict between man and the universe, the individual and society, good and evil, good and evil, in terms of life and death. Through impressive images, the author emphasizes that the real purpose of human existence in this bright world should be to serve members of society like himself, grateful and unselfish, to strive for regular goodness. Simulation devices have a special place in the success of the author’s "Woman in the Sand." It details abstract concepts and situations through simulation constructions. Even in order to get to the essence of the simulation devices in his works, it is sometimes necessary to be aware of Japanese linguoculturalism.